Dynamics of harmonically excited, reacting bluff body wakes near the global hydrodynamic stability boundary. (21st August 2015) - Emerson, Benjamin; Lieuwen, Tim
Abstract : This paper describes linear and nonlinear interactions between forced axial acoustic oscillations and the global mode of the reacting wake. This work is motivated by the problem of combustion instabilities, where acoustic oscillations associated with natural combustor modes excite hydrodynamic instabilities of the flow that, in turn, induce heat release oscillations. Wake flows with density stratification can be globally stable or unstable at high Reynolds numbers, and so the density change across the flame has significant influence on the natural flame and flow dynamics. Measurements were obtained in a facility in which flame density ratio, lip velocity and forcing frequency are independently varied using 5 kHz particle image velocimetry and Mie scattering measurements. By varying the density ratio, the hydrodynamic global mode growth rate can be systematically varied. In addition, measurements and analyses were performed where the forcing frequency is varied relative to the global mode frequency. While axial forcing excites a varicose response of the shear layers, the sinuous mode is the most rapidly growing. As expected, forcing at a frequency near the wake's global mode frequency leads to rapid growth in vortical disturbance amplitude, and the symmetric vortices quickly stagger as they convect downstream leading to a large scale, sinuous flapping of the wake and flame. A linear, local stability analysis, together with a nonlinear analysis, help elucidate the physics that govern the vortex staggering. The study concludes with an analysis of the heat release dynamics. Significantly, the study shows that the heat release exhibits quite different sensitivities than the fluid dynamics; e.g. axial forcing of the flow near its global mode frequency leads to a reduction in heat release oscillations. This is true even though this forcing frequency maximizes the local degree of vortically induced flame flapping. Thus, the results of this study show some phenomena that contradict conventional notions, namely that conditions which align the frequency of a hydrodynamic global mode with that of an acoustic mode may lead to diminished forced heat release oscillations in bluff body combustors.